Psychological evaluation for patients with non-cured facial nerve palsy. Issue 1 (February 2022) - Fujiwara, Keishi; Fukuda, Atsushi; Morita, Shinya; Yanagi, Hiroko; Hoshino, Kimiko; Nakamaru, Yuji; Furuta, Yasushi; Homma, Akihiro
Abstract: Objective: The aim of the present study was to evaluate the psychological condition of patients with non-cured facial nerve palsy and to investigate whether their psychological condition is correlated with the degree of facial nerve palsy, synkinesis or quality of life. Methods: Thirty patients with non-cured facial nerve palsy were enrolled in this study. Psychological conditions were evaluated by questionnaires including State-Trait Anxiety Inventory and Self-rating Depression Scale. Results: Of the thirty patients with non-cured facial nerve palsy, 17 (56.7%) and 15 patients (50.0%) felt anxiety and depression, respectively. Although there were no significant correlations between their psychological condition and the degree of facial nerve palsy or that of sequelae, significant correlations were observed between psychological condition and the degree of QOL, especially in terms of social function. Conclusions and significance: Disabilities associated with facial nerve palsy may be overlooked when evaluation is performed by physician-graded instruments alone. To resolve this problem, patients with non-cured facial nerve palsy should be evaluated by not only physician-graded tools but also patient-based assessment tools.